1985
DOI: 10.1152/jappl.1985.58.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Role of muscle mass and mode of contraction in circulatory responses to exercise

Abstract: The roles of the mode of contraction (i.e., dynamic or static) and the active muscle mass as determinants of the cardiovascular responses to exercise were studied. Six healthy men performed static handgrip (SHG), dynamic handgrip (DHG), static two-knee extension (SKE), and dynamic two-knee extension (DKE) to local muscular fatigue in approximately 6 min. Increases in mean arterial pressure were similar for each mode of contraction, 29 +/- 5 and 30 +/- 3 mmHg in SHG and DHG and 56 +/- 2 and 48 +/- 2 mmHg in SKE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
95
2
6

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 16 publications
9
95
2
6
Order By: Relevance
“…The different active muscle mass between the recent and present studies must have induced the different changes in the TPR in the repetitive contraction. It has been indicated that the TPR decreases from the baseline more with the increase in active muscle mass during dynamic exercise [6,7], but it does not change from the baseline during static exercise irrespective of active muscle mass [10,25,26]. In fact, Stebbins et al [10] showed that the repetitive handgrip contraction caused no change in the TPR from the baseline, which was at a level similar to that in the sustained one in the recent study.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The different active muscle mass between the recent and present studies must have induced the different changes in the TPR in the repetitive contraction. It has been indicated that the TPR decreases from the baseline more with the increase in active muscle mass during dynamic exercise [6,7], but it does not change from the baseline during static exercise irrespective of active muscle mass [10,25,26]. In fact, Stebbins et al [10] showed that the repetitive handgrip contraction caused no change in the TPR from the baseline, which was at a level similar to that in the sustained one in the recent study.…”
Section: Discussionmentioning
confidence: 75%
“…In these studies, however, small muscle groups were used as active muscles, which were triceps surae muscles in anesthetized cats [9] and forearm muscles in conscious humans [10]. The recruited small muscle group could be the factor resulting in similar or greater pressor response in the repetitive contraction compared to the sustained contraction because the pressor response to dynamic exercise with the recruitment of large muscles is smaller than that with the recruitment of small muscles, which is due to more reduction in total peripheral resistance (TPR) with the active muscle mass [6,7]. Thus the effect of large muscle recruitments on the different pressor responses to between static and dynamic contractions remained unknown.…”
mentioning
confidence: 99%
“…Previous studies attempting to compare the pressor response to dynamic and static contraction have used dynamic conditions with a lower TTI (12,21) or equated conditions on whole body oxygen uptake (3,5), which likely also results in a lower intensity in the dynamic condition due to higher muscle blood flows (35). We used the same handgrip protocol described by Stebbins et al (35), who demonstrated that peripheral diastolic, systolic and mean pressures were similar in response to static and dynamic contraction performed at 30% MVC and at the same TTI.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the blood pressure response during exercise has relationships with exercise intensity, duration and active muscle mass. 32,33 It is also known that although ECC includes less active muscle mass than CON [34][35][36][37] its exerted muscle strength is higher than CON. 16,31 Therefore, it might be thought that the active muscle mass in CON increases more than in ECC and that the accompanying significant vasopressor response increases the load on blood vessels.…”
Section: Discussionmentioning
confidence: 99%